Spinal Intradural Extramedulary Capillary Hemangioma Mimicking Meningioma - Moeinadin Safavi; Shahriar Dabiri (Iranian Society of Pathology, 2016)
Hemangiomas are considered as vascular malformations which are categorized by the type of vascular channel to capillary, cavernous, venous or arteriovenous(1). Their usual locations are soft tissue , cutaneous or subcutaneous tissue and bone especially vertebra(2).However, intradural extramedullary hemangiomas are rare and most of them fall in cavernous type category. Hereby, authors report a woman with spinal intradural extramedullary capillary hemangioma which is exceedingly rare.